From Berlin to Rome: The Case of Dora Friedländer in the Jungian Diaspora from Nazi Germany - Innamorati, Marco; Fiorani, Matteo (European Yearbook of the History of Psychology, 2024)
Abstract The protagonists of the Jewish diaspora from Germany following the rise of Nazism included not only many Freudian psychoanalysts but also several followers of Jung. Among them were Ernst Bernhard, who founded analytical psychology in Italy, and his wife Dora Friedländer. However, while studies have already been dedicated to Bernhard, little or nothing has been written about Dora, who was herself an important figure in the spread of Jungian culture in Italy. The article describes her cultural personality and the also mutually forming relationship she had with Bernhard.